If $x^2 + (4 - \sqrt{3}) x - 1 = 0, $ then what is the value of $x^2 +\frac{1}{x^2}$ ? |
$9-8\sqrt{3}$ $21-12\sqrt{3}$ $21-8\sqrt{3}$ $17-8\sqrt{3}$ |
$21-8\sqrt{3}$ |
We know that, If x - \(\frac{1}{x}\) = n then, x2 + \(\frac{1}{x^2}\) = \(\sqrt {n^2 + 2}\) If $x^2 + (4 - \sqrt{3}) x - 1 = 0, $ then what is the value of $x^2 +\frac{1}{x^2}$ Divide the given equation by x on the both sides, then we get, x - \(\frac{1}{x}\) = $(\sqrt{3} - 4)$ then, x2 + \(\frac{1}{x^2}\) = \(\sqrt {(\sqrt{3} - 4)^2 + 2}\) x2 + \(\frac{1}{x^2}\) = \(\sqrt {3 + 16 - 2×4×\sqrt{3} + 2}\) = $21-8\sqrt{3}$ |